2020
DOI: 10.3389/fnut.2020.593735
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Fiber Intake and Non-alcoholic Fatty Liver Disease in Adults

Abstract: Background: Evidence on the association of non-alcoholic fatty liver disease (NAFLD), a public health concern, with dietary fiber intake is inconsistent. Objective: To investigate the relationship between dietary fiber intake from different sources and NAFLD risk in US adults. Methods: Data were collected from the 2007-2014 National Health and Nutrition Examination Survey. NAFLD was defined as a United States Fatty Liver Index ≥30, and dietary fiber intake was assessed through two 24-h dietary recall interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 40 publications
3
34
1
Order By: Relevance
“…Recently, a study performed in a Dutch population found that subjects with a high fatty liver index (FLI) consumed less fibre daily, compared to those with a low FLI [ 117 ]. Similar results were also obtained in a subgroup of 6613 US adults participating in the National Health and Nutrition Examination Survey [ 132 ]. However, it is not fully known whether the protective effect of fibre against NAFLD is due to an indirect action through modulation of the microbiome or if it is a result of the direct anti-inflammatory properties of fibre [ 71 ].…”
Section: Nutrition and Nafldsupporting
confidence: 83%
See 1 more Smart Citation
“…Recently, a study performed in a Dutch population found that subjects with a high fatty liver index (FLI) consumed less fibre daily, compared to those with a low FLI [ 117 ]. Similar results were also obtained in a subgroup of 6613 US adults participating in the National Health and Nutrition Examination Survey [ 132 ]. However, it is not fully known whether the protective effect of fibre against NAFLD is due to an indirect action through modulation of the microbiome or if it is a result of the direct anti-inflammatory properties of fibre [ 71 ].…”
Section: Nutrition and Nafldsupporting
confidence: 83%
“…The relationship between fibre intake and NAFLD has been assessed in several observational studies and in a small number of small clinical trials with conflicting results. Although most of the studies suggest that high daily fibre consumption is associated with a preventive effect against NAFLD, other authors have not confirmed these results [ 132 ]. Recently, a study performed in a Dutch population found that subjects with a high fatty liver index (FLI) consumed less fibre daily, compared to those with a low FLI [ 117 ].…”
Section: Nutrition and Nafldmentioning
confidence: 99%
“…A meta-analysis showed that omega-3 PUFAs can decrease liver fat, ALT, AST and GGT in patients with NAFLD (46) . On the other hand, Zhao et al (47) found an inverse correlation between dietary fiber intake and NAFLD risk in the general population.…”
Section: Discussionmentioning
confidence: 97%
“…Our study is the first human RCT investigating the effect of insoluble cereal fibre on measures of visceral adiposity and NAFLD. While cohort studies consistently imply a role of non‐digestible carbohydrates in the prevention of NAFLD and the accumulation of visceral fat, [ 15,16,18,19 ] RCTs in humans are still sparse and were mainly using whole grain food products rather than specific fibre supplements. [ 20 ] Several rodent trials indicate, that both inflammation and liver fat content could be reduced by interventions with cellulose and other types of insoluble fibre.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13,14 ] Still, high intake of insoluble cereal fibre is associated with a reduced risk for NAFLD, showing stronger effect sizes than fruit and vegetable fibre, both of which are mainly soluble. [ 15,16 ] While there is not a single human RCT, specifically investigating the effect of insoluble dietary fibre on liver fat, there is at least some preclinical evidence for such effects in rats. [ 17 ] In humans, subjects with higher intake of insoluble fibre have smaller visceral adipose tissue depots.…”
Section: Introductionmentioning
confidence: 99%